Strategies for water management under limited water supply - Chandana, P (Indian Farming, 2020)
Irregular or insufficient rainfall can be a serious limitation to agricultural production, causing low yields and even crop failure. This is particularly true in drylands, where productivity levels are generally low. Irrigation water may be inadequate due to drought, lost well capacity, or changes in operation or administration of project water. When irrigation water is not available to meet crop demand, strategies are needed to achieve the highest possible economic return with limited water.